(untitled) (Revista Direitos Humanos e Democracia, 2026)
The article in question presents considerations about the reality of elderly people deprived of their liberty in Brazil. The general objective of the research being developed is to understand how the social reality of elderly people deprived of liberty in Rio Grande do Sul is constituted, in order to relate it to the scope of state social protection. Methodologically, the research is constituted as having a mixed focus, materialized in two moments: a) Bibliographic Moment and b) Documentary Moment. The bibliographic collection was carried out by mapping scientific articles published between the years 2019 and 2024, using content analysis, under the bias of the critical dialectical method. In terms of results, it was evidenced that the incarceration of elderly people is permeated by expressions of social issues, such as poverty. Among the challenges of prison, precarious survival conditions that disregard human rights emerge with greater intensity. The main crimes committed by elderly men involve sexual abuse and drug trafficking among elderly women. Prison situations are aggravated by legislative inconsistencies regarding the chronological recognition of old age, which limit access to rights. It is concluded that in the Brazilian prison system the so-called social (lack of) protection of elderly people persists, since they are neglected regarding the particularities of aging.